Overview of Nutritional Status, Protein and Purine Intake in Gout Patients at Banyu Urip Community Health Center - Salsabila Febrianti; Inne soesanti; Nuning Marina Pengge; Nurul Hindaryani (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Gout is a metabolic disorder influenced by diet, nutritional status, and lifestyle, and may lead to serious complications. However, limited data are available on the dietary and nutritional profiles of gout patients in primary healthcare. This study aimed to describe the nutritional status, protein intake, and purine consumption among gout patients at the Banyu Urip Community Health Center, Surabaya. A descriptive quantitative design was used from October 2023 to April 2024, involving 50 respondents selected by purposive sampling. Data were collected through anthropometric measurements, digital uric acid testing, and 2×24-hour dietary recall, then analyzed using descriptive statistics in SPSS. Results showed that 52% of respondents had hyperuricemia, 36% had overnutrition or obesity, and 52% consumed excessive protein. Additionally, 34% had high to very high purine intake. Excessive intake was predominantly observed among individuals with excess body weight. The study highlights a high prevalence of hyperuricemia, overnutrition, and excessive protein and purine intake, underscoring the need for targeted dietary counseling and lifestyle interventions at the primary healthcare level.